A collaborative effort of China in combating COVID-19 - Bangura, Mohamed S. (Glob Health Res Policy, 2020)
A novel coronavirus (COVID-19) was firstly identified in Wuhan by the end of 2019. China has implemented a series of preventive measures to deter COVID-19 spread and its consequences since the beginning of the epidemic. In China, the expansion of COVID-19 has been slowed down significantly through the effort of all contributors, including governments, nongovernments, and civil society. All collaborators have been actively involved in combating the epidemic, using their respective strengths to play their roles. China has mitigated the number of cases due to the mobilization of the whole society and collaborators joining collective efforts and actions in solidarity to tackle and conquer the virus. To date, China has continued to implement actions to control any resurgence of new cases of COVID-19 and keep its population safe. The people’s united effort against the virus has enhanced a great insight into China, and it might serve as a model to the global community in fighting the COVID-19 pandemic  in terms of coordination, solidarity, decisiveness, and leadership.